HMGB1-BoxA gene therapy in reversing cisplatin resistance in non-small cell lung cancer. - Nattapong Puthdee; Van-Hieu Mai; Sirapat Settayanon; Pithi Chanvorachote; Chatchawit Aporntewan; Apiwat Mutirangura; Chanida Vinayanuwattikun (PLoS ONE)
Cisplatin is a widely used chemotherapy agent in the treatment of non-small cell lung cancer (NSCLC). However, its clinical efficacy is limited by the development of drug resistance in patients with NSCLC. Recently, we demonstrated that HMGB1-BoxA gene therapy (BoxA) is an ideal cancer treatment that revitalizes normal cells while promoting cancer cells' DNA break cascade. Increasing cytoplasmic HMGB1 is a reason for cisplatin resistance (Cis-R); in this study, we investigated the potential of BoxA to reverse acquired cisplatin resistance in two NSCLC cell lines, A549/Cis-R, and H460/Cis-R. The growth capacity of these cancer cells was significantly impaired upon BoxA treatment, resulting in a notable reduction in cell viability, colony formation, cancer stemness, and self-renewal capacity. Significantly, BoxA enhanced cisplatin sensitivity and promoted apoptosis in cisplatin-treated Cis-R cells. Furthermore, BoxA altered the subcellular localization of the HMGB1 protein, decreasing its cytoplasmic localization. BoxA can potentially reverse cisplatin resistance by altering the translocation of HMGB1.